2021
DOI: 10.3390/jrfm14070288
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Risk Rating Agencies Decisions on Economic Growth and Investment in a Developing Country: The Case of South Africa

Abstract: Over the last decade, the South African economy has endured prevailing economic challenges, including weak economic growth, unreliable electricity supply, rising fiscal deficits, declining investment inflows and the inexorable rise in government debt alongside the expected impact of the coronavirus pandemic. Credit ratings have significantly evolved, making them key elements in the modern financial markets because of their creditworthiness opinions, as many investors across the globe rely heavily on their opin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Similar results were estimated by Meyer (2021) in an assessment of the Visegrad countries. Meyer and Mothibi (2021) investigated the impact of risk rating agencies' decisions on economic growth and domestic investment in South Africa from 1994 to 2020. Results indicated that significant longrun relationships exist between economic growth, the risk rating index as developed by the authors, and domestic investment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similar results were estimated by Meyer (2021) in an assessment of the Visegrad countries. Meyer and Mothibi (2021) investigated the impact of risk rating agencies' decisions on economic growth and domestic investment in South Africa from 1994 to 2020. Results indicated that significant longrun relationships exist between economic growth, the risk rating index as developed by the authors, and domestic investment.…”
Section: Literature Reviewmentioning
confidence: 99%